2011
DOI: 10.1080/1745039x.2011.623047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a microencapsulated feed additive of lactic and formic acid on the prevalence ofSalmonellain pigs arriving at the abattoir

Abstract: The main objective of this work was to investigate the potential of a microencapsulated mixture of organic acids (formic and lactic acid) added to the feed of fattening pigs to reduce the prevalence and shedding of Salmonella when arriving to the abattoir. Two trials were performed. In Trial 1, 24 fattening pigs received one of three diets: a control diet, the same diet including lactic and formic acid (0.4% each) (non-protected blend; NPB), or a lipid microencapsulated blend (0.14% each acid) (protected blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…These effects were most pronounced when the essential oils and organic acids were microencapsulated, which improved the ability of these acids to reach the large intestine and remain active (MEUNIER et al, 2006). The changes in the AGV levels observed in this study also corroborate those observed by Grilli et al (2010) and Willamil et al (2011), who revealed that microencapsulated organic acids can modify and improve cecal fermentation.…”
Section: Resultssupporting
confidence: 80%
“…These effects were most pronounced when the essential oils and organic acids were microencapsulated, which improved the ability of these acids to reach the large intestine and remain active (MEUNIER et al, 2006). The changes in the AGV levels observed in this study also corroborate those observed by Grilli et al (2010) and Willamil et al (2011), who revealed that microencapsulated organic acids can modify and improve cecal fermentation.…”
Section: Resultssupporting
confidence: 80%
“…The probable mode of actions of organic acids includes reducing the pH value of digesta in the gastrointestinal tract (Ravindran and Kornegay, 1993), regulating the balance of microbial populations in the gut, stimulating the secretion of digestive enzyme (Thaela et al, 1998), and promoting the growth and recovery of the intestinal morphology (Galfi and Bokori, 1990). According to Willamil et al (2011), microencapsulated acids significantly modify caecal fermentation. Galfi and Bokori (1990) reported that sodium-butyrate supplementation in piglets reduced coliform bacteria and increased the number of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hydrothermal treatment can reduce InsP 6 in grains and could therefore lead to a further reduction in InsP 6 concentration when combined with LA treatment [16][18]. Because LA treatment can have additional benefits on health and performance in livestock animals [19][24], treatment of barley with LA may be of interest in animal feeding. We hypothesized that soaking barley in increasing concentrations of LA in combination with heat may exert an additive effect on InsP 6 hydrolyzing properties.…”
Section: Introductionmentioning
confidence: 99%